Cryptotanshinone induces cell cycle arrest and apoptosis through the JAK2/STAT3 and PI3K/Akt/NFkB pathways in cholangiocarcinoma cells - Ke FY; Wang Z; Song XL; Ma Q; Hu YP; Jiang L; Zhang YJ; Liu YB; Zhang Y; Gong W (Drug Design, Development and Therapy, 2017)
Fayong Ke,1,2,* Zheng Wang,1,2,* Xiaoling Song,1,2 Qiang Ma,1,2 Yunping Hu,2 Lin Jiang,2 Yijian Zhang,2 Yingbin Liu,1,2 Yong Zhang,1 Wei Gong1,2 1Department of General Surgery, Xinhua Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 2Institute of Biliary Disease Research, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China *These authors contributed equally to this work Background: Cholangiocarcinoma (CCA) is the most common biliary tract malignancy in the world with high resistance to current chemotherapies and extremely poor prognosis. The main objective of this study was to investigate the inhibitory effects of cryptotanshinone (CTS), a natural compound isolated from Salvia miltiorrhiza Bunge, on CCA both in vitro and in vivo and to explore the underlying mechanisms of CTS-induced apoptosis and cell cycle arrest. Methods: The anti-tumor activity of CTS on HCCC-9810 and RBE cells was assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide (MTT) assay and colony forming assays. Cell cycle changes were detected by flow cytometric analysis. Apoptosis was detected by annexin V/propidium iodide double staining and Hoechst 33342 staining assays. The efficacy of CTS in vivo was evaluated using a HCCC-9810 xenograft model in athymic nude mice. The expression of key proteins involved in cell apoptosis and signaling pathway in vitro was analyzed by Western blot analysis. Results: CTS induced potent growth inhibition, S-phase arrest, apoptosis, and colony-forming inhibition in HCCC-9810 and RBE cells in a dose-dependent manner. Intraperitoneal injection of CTS (0, 10, or 25 mg/kg) for 4 weeks significantly inhibited the growth of HCCC-9810 xenografts in athymic nude mice. CTS treatment induced S-phase arrest with a decrease of cyclin A1 and an increase of cyclin D1 protein level. Bcl-2 expression was downregulated remarkably, while Bax expression was increased after apoptosis occurred. Additionally, the activation of JAK2/STAT3 and PI3K/Akt/NFκB was significantly inhibited in CTS-treated CCA cells. Conclusion: CTS induced CCA cell apoptosis by suppressing both the JAK2/STAT3 and PI3K/Akt/NFκB signaling pathways and altering the expression of Bcl-2/Bax family, which was regulated by these two signaling pathways. CTS may serve as a potential therapeutic agent for CCA. Keywords: cholangiocarcinoma, cryptotanshinone, apoptosis, JAK2/STAT3, PI3K/Akt/NFκB